"Owned and conducted entirely by the native Christian community": der "Christian Patriot" und die indigen-christliche Presse im kolonialen Indien um 1900 - Koschorke, Klaus (Studien zur außereuropäischen Christentumsgeschichte (Asien, Afrika, Lateinamerika), 2019)
The 'Christian Patriot' (Madras/Chennai 1890-1929) -- a journal "owned and conducted entirely" by Indian Christians -- represents a new class of documents for the study of the history of World Christianity. This weekly understood itself as mouth piece of the South Indian Protestant community "as a whole" and tried to assert their independent voice in the colonial public sphere. "Christian in tone and patriotic in its aims", it criticized both missionary paternalism and Hindu fundamentalism. At the same time, the 'Christian Patriot' reflects a wide range of transregional networks of indigenous Christian elites in Asia and other regions and colonial societies. Thus, this study contributes to a new understanding of Christian globality around 1910. --